Outcomes and prognosticators in regionally recurrent cutaneous squamous cell carcinoma of the head and neck. Issue 11 (November 2020) - Wilkie, Mark D.; Chudek, Dorota A.; Flynn, Christian D.; Gaskell, Peter; Loh, Christopher; Tandon, Sankalap; Roland, Nicholas J.; Jones, Terence M.; Lancaster, Jeffrey
Abstract: Introduction: Data regarding regionally metastatic cutaneous squamous cell carcinoma of the head and neck (cSCCHN) is limited and derived almost exclusively from Australian and United States (US) institutions. We report the first United Kingdom perspective, with the aims of benchmarking survival outcomes and identifying clinically relevant prognosticators. Materials and methods: Ninety-one patients with regionally recurrent cSCCHN treated with curative intent over a ten-year period (2009–2018) were studied retrospectively. Time-to-event analyses were used to estimate oncological outcomes, and log-rank statistics and Cox proportional hazards models used to examine potential prognosticators. Receiver operating characteristics were also used to analyse the influence of nodal disease burden. Results: Parotid involvement (with or without neck involvement) was most common (79.2%), and time to recurrence in those with parotid disease alone significantly shorter than for any other disease distribution (p = 0.034). Respective five-year overall, disease-specific, and disease-free survival estimates were 43.8%, 63.8%, and 36.2%. Extracapsular spread (ECS) portended reduced DFS and DSS (p = 0.012 and p = 0.005 respectively). Increasing nodal burden (≥4 involved nodes) also reduced DSS (p = 0.020), while parotid disease alone predicted more favourable DSS (p = 0.008). ECS and isolated parotid involvement remained significant on multi-variate analysis (p = 0.014 and p = 0.028 respectively). Conclusions: Oncological outcomes were unfavourable but broadly consistent with previous reports, notionally lending support to a more proactive approach in managing the clinically node negative neck/parotid in selected high-risk cases. Our data also support distinct parotid classification and consideration of involved lymph node number in future staging systems.